Leadership perspectives on service delivery in the South African Public Service : a critical overview of the public financial management systems from 1994 to 2004 - Fourie, D.J. (David Johannes) (University of Pretoria, 2013)
Thesis (DPhil)--University of Pretoria, 2006.